Biomass production and fatty acid accumulation in Chlorella sp. (strain DEC1B) isolated from a petrol refinery in Huelva (Spain). Issue 2 (21st April 2016) - Ruiz‐Domínguez, Mari Carmen; Vaquero, Isabel; Rivas, Mariella; Zapata, Manuel; Mogedas, Benito; Márquez, Mayca; Gómez, José; Larraz, Rafael; Frontela, Juana; Vega, José M.; Vílchez, Carlos
Summary: A microalgal strain was established from Cepsa's refinery wastewater treatment plant in Huelva (southwest of Spain). Genetic analysis of the chloroplastic rbc L gene encoding for the large subunit of the ribulose bisphosphate carboxylase enzyme (Rubisco) showed the strain had high homology with other known rbc L sequences of the genus Chlorella . The strain grows well autotrophically in minimum mineral medium, with a growth rate of 0.28 ± 0.012 day −1 and a biomass productivity of 138.9 ± 6.7 mg L −1 day −1 . N‐starvation and/or over illumination with 650 µmol photons m −2 s −1 of PAR light on the cultures induced a significant increase in the intracellular content of lipids in this microalga. Total lipids were extracted from the strain biomass with 2:1 chloroform‐methanol, and they accounted for approximately 50% of the dry biomass. Polyunsaturated fatty acids (PUFAs) represented 60.4% of the total fatty acids found in the strain, thus making this biomass attractive as a high added‐value product source. The strain was able to grow efficiently in the refinery treated wastewater from which it was isolated, providing an attractive advantage for further development of more sustainable algal biomass production processes at reduced costs close to a petrol refinery area.